A Flavonoid Rhamnoside from the Seeds of Nephelium lappaceum Linn. (Rambutan) - Ditya Marissa; Hafidz Kamarul Hadj; Anis Shofiyani; Endah Sayekti; Rudiyansyah, Rudiyansyah (The Journal of Pure and Applied Chemistry Research, 2026)
Nephelium lappaceum L. (Rambutan) is a renowned seasonal fruit in Southeast Asia and has been cultivated for centuries in tropical regions. Research on the phytochemicals of this plant are scarce. Rambutan seeds are known to contain phenolics and flavonoids as the primary constituents. Unfortunately, the flavonoid structures in rambutan seeds remain unexamined. This study presents the extraction and structural elucidation of a flavonoid glycoside from the ethyl acetate fraction of N. Lappaceum seeds. Methanol crude extract of N. Lappaceum seeds was acquired through maceration and subsequently partitioned between n-hexane and ethyl acetate. Various chromatographic methods, such as vacuum liquid chromatography (VLC), column chromatography (CC), and preparative thin-layer chromatography (PTLC), were employed on the ethyl acetate fraction to obtain compound 1. Phytochemical assays employing 10% NaOH, Shinoda, and 5% FeCl3 on compound 1 demonstrated the presence of a flavonoid. According to the NMR data (1D and 2D) and HRTOF-MS-ES, compound 1 was characterised as the flavonoid glycoside, kaempferol-7-O-α-rhamnose or α-rhamnoisorobin.